Dødsspring til Hest fra Cirkuskuplen - Brand, Neil (Danish Silent Classics, 2004)
A loosely framed plot serves to connect a series of sensational scenes such as an escape from a burning hotel, a laison with a promiscuous woman and a dangerous circus act with a horse. [www.lib.berkeley.edu]